Responding to the climate emergency: how are UK universities establishing sustainable workplace routines for flying and food?. (9th August 2021) - Hoolohan, Claire; McLachlan, Carly; Jones, Christopher; Larkin, Alice; Birch, Christina; Mander, Sarah; Broderick, John
ABSTRACT : Scope 3 emissions from the UK higher education sector are globally significant, and long-distance air travel and catering are particularly emissions-intensive aspects of workplace routine. They each present complex problems, as transition to low-carbon alternatives requires the reconfiguration of professional practices. This paper examines the sustainability policies of 66 UK universities to establish the extent to which planning and action in these areas are commensurate with climate emergency declarations. The findings indicate that universities recognize their role in creating demand for long-distance travel and sustaining high-carbon diets. However, few have specific emissions reduction targets or action plans that would rapidly and substantially reduce emissions in these areas. Discussion focuses on two core points; first, how greater cohesion in reporting and target-setting can be achieved across the sector to raise the ambition of targets and intervention; and second to identify opportunities for institutions to disrupt and reshape professional practices to reduce emissions in these areas. Key Policy Insights Reducing emissions in the higher education sector requires organizations to foster low-carbon academic practices by engaging with the systemic cultural and material conditions that support high-carbon academic practices. The establishment of robust targets, action plans and monitoring processes would further support sector-wide decarbonization, and require consensus across HE institutions and governing bodies. Sector-wide agreement on the level and pace of emissions reduction will help to accelerate ambition regarding Scope 3 emissions reduction and determining the appropriate contribution of different institutions will help identify where action is most urgently required. Findings suggest a need for absolute targets for emissions reduction associated with long-distance travel, and that food policies focus on achieving a volumetric reduction in the weight of meat served so that absolute levels of greenhouse gas emissions are reduced. Travel and food provision are complex aspects of university emissions, but a climate emergency framing requires all organizations to use their full range of influence to rapidly and substantially reduce emissions.